On the Uniform Convergence of Fourier Series on a Closed Domain - Rakhimov, Abdumalik Abdumadjidovich (Eurasian Mathematical Journal, 2017)
The uniform convergence on a closed domain is studied of eigenfunction expansions of continuous functions belonging to function spaces with mixed norm.